(untitled) (Research, Society and Development, 2022)
Currently, Diabetes Mellitus has great relevance in public health and among the immeasurable problems that diabetes can cause in patients with high blood glucose is Depression, whose lack of investigation, monitoring and treatment of the disease favors the progression of consequences. The present research aimed to evaluate the level of knowledge of diabetic patients, treated at the Unified Health System (SUS) in the Boa Vista/Roraima city, regarding the relationship between Diabetes and Depression. The research was a cross-sectional, descriptive, quantitative study, carried out through the application of a semi-structured form to 150 diabetic people, users of the SUS, in the city of Boa Vista - RR, during the year 2021. The total sample, most individuals did not receive any explanation about the connection between Diabetes and Depression. Among those who claimed to have received some guidance, more than half said they received it from a health professional at the UBS. In addition, the majority of respondents reported being unaware of any type of treatment for the disease. This way, with depression being one of the most prevalent disorders associated with diabetes, the scenario is alarming, especially with the realization of the fact that there is such a low level of awareness regarding the link between the two diseases. It should also be noted that the service provided by the public health sector does not efficiently relay the correlation between the two.